A novel seawater and sea sand concrete-filled FRP-carbon steel composite tube column: Cyclic axial compression behaviour and modelling. (1st February 2022) - Zhang, Yirui; Wei, Yang; Miao, Kunting; Li, Bing
Highlights: Cyclic axial compression tests of 12 seawater and sea sand concrete-filled FRP- carbon steel composite tube (SFSCT) columns were conducted. The thickness and type of FRPs were used as variables to test the failure mode, envelope and plastic strain. The strain recoverable performance of FRPs is beneficial to the concrete shrinkage and the suppression of plastic strains. A new stress–strain model was developed for predicting the full cyclic stress–strain response. Abstract: This paper presents an experimental investigation of a novel seawater and sea sand concrete (SSC)-filled fibre-reinforced polymer (FRP)-carbon steel composite tube column (SFSCT) subjected to cyclic axial compression loadings. The proposed structure is covered with FRP on both the inner and outer walls of a traditional carbon steel tube to solve the corrosion problem of seawater and sea sand concrete and to improve considerably the mechanical properties of the structure at the same time. Cyclic axial compression tests for 12 SFSCTs and 2 concrete-filled steel tubes were carried out. The thickness and type of FRP were used as variables to assess the mode of failure, envelope, plastic strain and stiffness at unloading. The results show that FRP can confine effectively the lateral expansion of concrete. Carbon fibre-reinforced polymer (CFRP) has a better confinement performance than basalt fibre-reinforced polymer (BFRP). According to the different confinement mechanisms of the internal and external layers of FRP on concrete, a more reasonable cyclic stress–strain model was proposed, and the superiority of the proposed model was verified by comparison with the experimental results.